Combining O2 High Flow Nasal or Non-Invasive Ventilation with Cooperative Sedation to Avoid Intubation in Early Diffuse Severe Respiratory Distress Syndrome, Especially in Immunocompromised or COVID Patients? - Petitjeans Fabrice; Longrois Dan; Ghignone Marco; Quintin Luc (The Journal of Critical Care Medicine)
This overview addresses the pathophysiology of the acute respiratory distress syndrome (ARDS; conventional vs. COVID), the use of oxygen high flow (HFN) vs. noninvasive ventilation (NIV; conventional vs. helmet) and a multi-modal approach to avoid endotracheal intubation (“intubation”): low normal temperature, cooperative sedation, normalized systemic and microcirculation, anti-inflammation, reduced lung water, upright position, lowered intra-abdominal pressure.